Vincenzo la rosa (1941-2014) : un archeologo tra Sicilia e Egeo - Arcifa, Lucia,; Militello, Pietro, (Praehistorica Mediterranea ;, 2021)
This volume re-examines the scientific figure of Vincenzo La Rosa, professor of Aegean Civilisations at the University of Catania, exploring his contributions to our knowledge of the prehistory of Crete, Sicily and the Aegean, and to the application of a long-term perspective linking the ancient and modern worlds.